Granulometria do calcário calcítico na dieta de codornas japonesas após o pico de postura - Pereira, Isabelli Dias Brito (2021)
The use of nutritional strategies on quail production that preserves eggshell and bone quality are important to produce a great number of marketable eggs, which directly reflects on profitability of the production system. As quail ages, egg weight increases and the ability to use calcium is reduced, reflecting in worse shell quality and less calcium reserve in bone. The objective of this study was to evaluate the influence of limestone particle size on bone quality, egg quality and performance parameters of Japanese quails (Coturnix coturnix japonica) after production peak. 240 Japanese quails were used, aged 214 to 277 days old, distributed in a completely randomized design, with five treatments and six replications, with eight quails per experimental unit and an experimental period of 63 days. Two limestone particle sizes were used to formulate diets: coarse limestone with average geometric diameter (AGD) = 1.14mm and limestone considered fine AGD = 0.117mm. The treatments used were: T1 - diet with 100% coarse limestone; T2 – 70% coarse limestone and 30% fine limestone; T3 - 50% coarse limestone and 50% fine; T4 - 30% coarse limestone and 70% fine; T5 – diet with 100% fine limestone. The replacement of the coarse limestone by fine limestone does not influence performance, egg quality and bone quality of Japanese quails after production peak, aged 214 to 277 days old.